SINTESIS POLIMER TERCETAK MOLEKUL LANSOPRAZOL UNTUK PEMISAHAN DAN ANALISIS DALAM URIN - Stania Manihuruk, Christin
Molecularly Imprinted Polymer (MIP) is a polymer made with molecular printing techniques that have an affinity for the template so that MIP has a high selectivity and sensitivity for molecular recognition. Biological matrices i.e urine may interfere the analysis using the UV-Vis spectrophotometry method and concentration lansoprazole in urine is relatively small about 15- 30% of the dose so that needed preparation of samples for gaining a high accuracy and precision result. The aim of this study was to synthesize MIP with lansoprazol as a template for the separation of lansoprazole in urine and verification of the lansoprazol analysis method using UV- Vis spectrophotometer. MIP was synthesized using lansoprazol as a template, acrylamide as a monomer, EGDMA as a crosslinker, AIBN as initiator and methanol as a porogen solvent. MIP synthesis using a bulk polymerization method with ratio of the template:functional monomer:crosslinker is 1:4:20 in mol. Analyze MIP that has been done is IR spectrum, adsorption capacity, desorption capacity, and specificity. Molecularly Imprinted Polymer Solid Phase Extraction (MISPE) is made by adding a MIP into the SPE coloumn and in the same way used Non- Imprinted Polymer Solid Phase Extraction (NISPE) as a comparison. Testing of lansoprazole separation in urine was performed using MISPE and NISPE. Based on the research results, the recovery of lansoprazole in urine using MISPE and NISPE was 82.074% and 33.255%. The result of verification of analysis method was linearity value r2 = 0.9992; VXO = 0.3973%, the accuracy recovery was 98.714 - 101.542%, and the variance coefficient was 0.916%.